Investigation of Ambient Aromatic Volatile Organic Compounds in Mosimi Petroleum Products Depot, Sagamu, Nigeria - Ismail Muhibbu-din (Anthropogenic Pollution)
Among chemical industries, petroleum depots have been identified as large emitters of Volatile Organic Compounds (VOCs).They affect air quality and constitute serious health and environmental problems on the ecosystem. Air samples were collected over activated charcoal, using a low volume air sampler. The sampler was placed at a human breathing height of 1.5 m for a sampling period of 8 hours at seven different sampling locations as follows; Workshop area, Slop Tanks area, Gate 1, Tank Farm area, Gate 2, Otiyelu Village and Marketerâs Block. Desorption process was performed on the adsorbed activated charcoal using a solvent extraction method. The extracted solutions were subjected to Flame Ionization Detection analysis in a Gas Chromatograph using a capillary column HP 5MS with length, inner diameter and particle size set at (30 m Ã 0.25 mm Ã 0.25 Î¼m). The Gas Chromatograph was powered with ChemStation RevA09.01 software to determine the concentrations of each of the VOCs species present. The sampling collection and quantitative analysis described above is consistent with ANSI/ASTM D-1605-60 procedure. The identified VOCs species emitted were characterized by toluene (52.84%), benzene (37.61%), xylene (5.67%), and ethyl benzene (3.88%). The observed concentrations uncovered the air tolerance limits set by United States Environmental Protection Agency and the Agency for Toxic Substances and Diseases Registry.